Diagnosis of distance education among students and doctoral students with disabilities in the situation of the COVID-19 pandemic – selected issues of the research reporti - Gutowska, Anna; Sztobryn-Giercuszkiewicz, Joanna (Virtualizing the lives of people with disabilities, 2021)
The aim of the publication is to present selected results of the research on distance education of students with disabilities in Polish higher education institutions during COVID-19 pandemics. The authors gathered the opinions from 291 students with various disabilities, and they performed the analysis of the implementation of online education process in pandemics from the perspective of this specific group. The publication includes the respondents’ experiences referring to different areas of distance education and to its positive and negative aspects. It also offers the assessment of online learning from the substantive and organisational angle and from the perspective of its influence on the psychic, physic and social sphere of the respondents’ functioning. Also the opinions of students with disabilities on the support they expected and the one they received and on their expectations for distance education to be better adjusted to their needs are included in the publication. Perspectives of students with different disability types and levels, representing various higher education institutions, different study programmes, cycles and stages of studying were taken into consideration in the research.